2014
DOI: 10.1007/s10815-014-0176-5
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions among infertile couples of lifestyle behaviors and in vitro fertilization (IVF) success

Abstract: Purpose To assess how patients perceive various lifestyle behaviors impact IVF success. Methods Cross-sectional study of heterosexual, Englishspeaking couples (n=138) who completed web-based surveys during IVF treatment cycle. Perceived impact of lifestyle choices assessed by multivariable logistic regression and pvalue tests for linear trend (P t ). Result(s) During the IVF cycle, most patients consider it helpful for women to exercise (76 %), avoid stress (87 %) and limit activity after embryo transfer (92 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“… A prescription for an antidepressant does not guarantee that the medication was actually consumed, which could lead to women with a dispensation being misclassified as exposed. Women planning to become pregnant are often conscientious about lifestyle factors that could affect conception [125], and they may decide to discontinue their medication directly before or during their IVF cycle.…”
Section: Ascertainment Biasmentioning
confidence: 99%
“… A prescription for an antidepressant does not guarantee that the medication was actually consumed, which could lead to women with a dispensation being misclassified as exposed. Women planning to become pregnant are often conscientious about lifestyle factors that could affect conception [125], and they may decide to discontinue their medication directly before or during their IVF cycle.…”
Section: Ascertainment Biasmentioning
confidence: 99%
“…A prescription does not guarantee that the medication was actually consumed, which could lead to cycles being misclassified as exposed. Women planning to become pregnant are often conscientious about lifestyle factors that could affect conception (49), so they may be less compliant with their medication. Additionally, antidepressants are not exclusively prescribed for depression and anxiety, and can be prescribed for other indications.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Notably, women would provide 'knowledge' to male posters on particular topics, often reporting their partner's experiences or outcomes as supporting evidence for their posts. Other research has suggested that women may have greater awareness of lifestyle factors in relation to infertility (Hawkins et al 2014), and that women may be 'prescribers' of lifestyle regimes to their male partners (Porter and Bhattacharya 2008). Men can, however, claim agency in enacting lifestyle changes, and given that men themselves were seeking help and support this offers some evidence of male engagement in the reproductive realm.…”
Section: Discussionmentioning
confidence: 99%